Construction of a Business Intelligence environment for the Secretariat of Social Assistance of the Municipality of São Paulo (Research, Society and Development, 2021)
The Data Science field has become one of the most promising markets in the technology field in recent years. The use of sophisticated techniques and hardware and software resources to handle large volumes of data and provide integrated environments to assist in decision making in large and medium organizations has advanced its frontiers and reached several other sectors (public and private) that were previously restricted only to the transactional aspect of the databases. This paper aims to describe the conception, modeling and implementation of an information management environment of the Municipal Secretariat for Social Assistance and Development - SMADS of the Municipality of São Paulo, aiming at the modernization of the Secretariat's information management, qualifying the elaboration, implementation and monitoring of public social assistance policies implemented in the city of São Paulo. The methodology used was the bottom-up approach initially presented by Ralph Kimball as a proposal to develop a fast and understandable DW project. The creation of the DW followed the steps of the KDD Process: data selection; pre-processing; transformation; interpretation and analysis. The project was carried out through a partnership between the City of São Paulo and UNESCO and covered all stages of a Business Intelligence (BI) process. This work describes the steps of: identification of needs, implementation of operational infrastructure, construction of the Data Warehouse (DW), implementation of ETL processes, preparation of panels, preparation of documentation and training of different user profiles. The following data sources were used: database of legacy systems used by SMADS as well as several external databases with emphasis on the Federal Government's CadÚnico. The results contemplated the creation of a Business Intelligence environment and the dissemination of the culture of creation of data visualization models for the decision-making process within the scope of the Social Assistance Secretariat of the Municipality of São Paulo, which allowed a better efficiency in the application and monitoring of public social assistance policies in the city of São Paulo.